New Dibenzo-α-pyrone Derivatives with α-Glucosidase Inhibitory Activities from the Marine-Derived Fungus Alternaria alternata - Jinxin Zhang; Baodan Zhang; Lei Cai; Ling Liu (Marine Drugs, 2022)
Three new dibenzo-α-pyrone derivatives, alternolides A–C (1–3), and seven known congeners (4–10) were isolated from the marine-derived fungus of Alternaria alternata LW37 assisted by the one strain-many compounds (OSMAC) strategy. The structures of 1–3 were established by extensive spectroscopic analyses, and their absolute configurations were determined by modified Snatzke′s method and electronic circular dichroism (ECD) calculations. Compounds 6 and 7 showed good 1,1-diphenyl-2-picrylhydrazyl (DPPH) antioxidant scavenging activities with IC50 values of 83.94 ± 4.14 and 23.60 ± 1.23 µM, respectively. Additionally, 2, 3 and 7 exhibited inhibitory effects against α-glucosidase with IC50 values of 725.85 ± 4.75, 451.25 ± 6.95 and 6.27 ± 0.68 µM, respectively. The enzyme kinetics study indicated 2 and 3 were mixed-type inhibitors of α-glucosidase with Ki values of 347.0 and 108.5 µM, respectively. Furthermore, the interactions of 2, 3 and 7 with α-glucosidase were investigated by molecular docking.